THE IMPACT OF CONTENT MARKETING, PRODUCT QUALITY, AND HEDONIC MOTIVATION ON IMPULSIVE BUYING BEHAVIOR - Wijayanti, Herlin; Handayani, Jati; Muslikh, Moh.; Prihatiningsih, Prihatiningsih; Winarni, Winarni (International Conference on Vocational Business, Logistic, Accounting, Supply Chain, Tax (ICoBLAST); Vol 1, No 1 (2026): 1st ICoBLAST, 2026)
The rapid advancement of information technology has reshaped human life, extending beyond communication to influence education, work, entertainment, and commerce. In Indonesia, internet penetration reached 79.5% in 2024 with 221.6 million users, supporting the rapid rise of e-commerce. Indonesia is now the fastest-growing e-commerce market in the world, recording a growth rate of 30.5%, far above the global average of 10.4%. Within this context, Shopee has become the leading platform, recording 2.3 billion visits in 2023 and surpassing its competitors. The central issue explored in this study is the inconsistency in prior research regarding the effects of content marketing, product quality, and hedonic shopping motivation on impulsive buying, leading to the research question: How do these three factors influence impulsive buying behavior among Generation Z Shopee users in Central Java? The novelty of this study lies in integrating the three variables within the specific context of Shopee and Generation Z in Central Java, where more than 8.5 million digital natives reside. Previous studies have shown mixed results and rarely focused on this demographic, leaving an important gap in the literature. To address this, the research employed a quantitative causal design with data collected through an online questionnaire distributed to 100 Generation Z Shopee users using purposive sampling. The data were analyzed with multiple linear regression, supported by F-tests, t-tests, and the coefficient of determination (R²). The findings indicate that content marketing, product quality, and hedonic shopping motivation simultaneously have a significant effect on impulsive buying, with an adjusted R² of 0.803. Partially, product quality and hedonic shopping motivation has a positive and significant influence, while content marketing has a negative but significant effect. These results show that impulsive buying among Generation Z is shaped by both external marketing strategies and internal motives, with product quality and enjoyable shopping experiences acting as stronger drivers than aggressive promotions. Keywords : Content Marketing; Product Quality; Hedonic Shopping Motivation; Impulsive Buying; Shopee JEL Classification : M31, M37, L86, D90, D91